Theater practices and elderly people: in search of resignification (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
By focusing on the articulation between theatrical practices and elderly people, the first part of this research found a reiterative discursiveness of theater as an instrument for improving the quality of life of the elderly. Trying to problematize this, a theoretical dialogue was sought with Denis Guénoun (2004) and his urgencies for contemporary theater; and Michel Foucault (2010), regarding his notions of norm. In the second part of the research, through the proposition of an artistic-pedagogical practice, a reflection was made on the elderly in scenic action as a possibility for improving the “quality of life” of contemporary theater, resulting in multiple displacements and resignifications.
Keywords: elderly; theater pedagogy; dramaturgy; biopolitics